“We are separating ourselves”: Effects of Demographic and Economic Change on Neighbor Relations in a Working-Class Neighborhood - Gimeno Monterde, Chabier; Esteban Carbonell, Elisa; Romero Martín, Sandra (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2024)
In the Spanish urban peripheries, built during the developmentalism of the dictatorship, popular classes have settled in two migratory cycles, one regional and the other international. Ethnic diversification, economic precarization and the absence of public policies against the deterioration of housing have made Las Fuentes (Zaragoza) the district with the lowest family income in the city. This economic and demographic evolution is attributed to the emergence of tensions characterized by the activation of ethnic group prejudice. This article analyzes these changes in the evaluation of coexistence based on focus groups and interviews. The results show that public services and concurrence in micropublics favor daily negotiation strategies that sustain conviviality. Meanwhile, the abandonment of public policies favors new tensions in the inner periphery, which concentrates the most deteriorated housing and the most precarious and stigmatized population of the neighborhood.